PEMANFAATAN SISA POTONGAN KAYU OLAHAN UNTUK PRODUK PAPAN LANTAI KOMPOSIT - Fakhri -; Haji Gussyafri; Syafruddin - (Jurnal APTEK, 2011)
Currently, the availability of commercial timberand the price decreases the more expensive, efforts are needed to optimize the utilization ofwood. One of the efforts to optimize use of wood can be done by utilizing the rest of sawn timber which has a small and short pieces into a form of veneer for the manufacture of composite floor boards. The purpose of this study is to calculate the efficiency of implementation and product prices of composite floor boards from wood waste material processed, the resulting product ofthe floor boards that can display a charming visual impression. Making the floor boards made of three models: model 1 in the form of composite laminated beams made from composite wood waste processed, and then sliced into several layers of floor boards; model 2 in the form of three layers of combined board cross between layers; model 3 in the form of a thick sheet board (as bottom layer) and on the top layer of veneerare arranged crossing. The results obtained by optimizing the utilization of wood waste processed in terms of technical and price more optimal processing using model 3.